Deep-learning based IC die identification and die surface defect inspection - Teo, Kai Yu (Nanyang Technological University, 2023)
Much effort is needed when detecting faults in semiconductors during the manufacturing process. With the rise of artificial intelligence to enhance processes, many would wonder how it is incorporated with semiconductor technologies. However, as a substantial amount of training data is required for the detection to be accurate, another concern comes along where a lot of time is required during the process of collecting data and processing these data thereafter.